Adherence Barriers for Adolescent and Young Adult Transplant Recipients: Relations to Personality. (14th April 2020) - Quast, Lauren F; Gutiérrez-Colina, Ana M; Cushman, Grace K; Rea, Kelly E; Eaton, Cyd K; Lee, Jennifer L; George, Roshan P; Blount, Ronald L
Abstract: Objective: Much of the extant literature on adherence barriers has focused on modifiable factors (e.g., knowledge, social support); however, less is known about how barriers may be associated with relatively stable constructs, such as personality traits. The current study examines associations between personality (i.e., agreeableness, conscientiousness, neuroticism) and adherence barriers in a group of adolescent and young adult (AYA) solid organ transplant recipients. Demonstrating associations between barriers and personality may help in understanding why barriers are stable over time. Additionally, different personality traits may relate to different types of barriers. Methods: The sample included 90 AYAs ( M age = 17.31; SD = 2.05; 58% male) who received a kidney ( n  =   36), liver ( n  =   29), or heart ( n  =   25) transplant at least 1 year prior to study enrollment. AYAs completed the Agreeableness, Conscientiousness, and Neuroticism scales from the NEO Five-Factor Inventory and the Adolescent Medication Barriers Scale (AMBS). Results: Lower levels of agreeableness and conscientiousness and higher levels of neuroticism were related to higher self-reported barrier scores (AMBS; r' s = .31– .53, p' s < .001). The relations differed by personality factor and barrier type. Conclusion: Adherence barriers showed medium to large associations with personality traits that are known to be relatively stable. Our findings indicate that the temporal stability of barriers to adherence may be due in part to their association with relatively enduring personality characteristics.